'Somebody Else's Roadmap': Lived Experience of Maudsley and Family‐based Therapy for Adolescent Anorexia Nervosa. Issue 3 (22nd October 2017) - Conti, Janet; Calder, Jamie; Cibralic, Sara; Rhodes, Paul; Meade, Tanya; Hewson, Daphne
Abstract : The Maudsley and more recent family‐based therapy manualised approaches are positioned by some as the gold standard, evidence‐based therapy for adolescent anorexia nervosa (AN). However, a significant proportion of adolescents and their families either discontinue this therapy and/or find that it simply does not work for them. These adolescents and families are under‐represented in the literature on therapeutic interventions for adolescent AN. This paper begins to address this gap with an in‐depth qualitative case study that explores the lived experience of Maudsley family therapy (MFT)/family‐based therapy (FBT) for one female adolescent (age 14 years) and her family over the period of 3 years (ages 11–14). Although initially handing over the responsibility for her eating was comforting and reinstated a sense of control in the family system, these experiences were not maintained. When she did not progress past the first phase of FBT, she and her family experienced the approach as blaming. She felt silenced and family alliances were weakened. This paper analyses how the family members negotiated and preserved their identities within this disabling context.